2013
DOI: 10.15578/squalen.v7i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyvinyl Alcohol-Chitosan Hydrogel and Study of Its Swelling and Antibacterial Properties

Abstract: The aim of this research was to synthesize a hydrogel for wound dressing by mixing of polyvinyl alcohol (PVA) and chitosan (CTS) and processed by combination technique of freezing-thawing and irradiation by gamma ray, and to study of its properties. PVA aqueous solution 10% (w/v) was mixed with 2% (w/v) chitosan (CTS) solution and homogenized. The PVA-CTS mixture was processed by freezing-thawing up to 3 cycles, and then irradiated by gamma rays at the dose ranged of 20-50 kGy (dose rate was 10 kGy/hour). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
3
9
0
1
Order By: Relevance
“…Cross-linked hydrogels ( Fig. 6b and 6c) show greater absorption capacity when the PVA is at higher concentrations, indicating a suitable cross-linking among molecules, in agreement with Wikanta [16]. Fig.…”
Section: Aloe Vera Absorptionsupporting
confidence: 80%
See 2 more Smart Citations
“…Cross-linked hydrogels ( Fig. 6b and 6c) show greater absorption capacity when the PVA is at higher concentrations, indicating a suitable cross-linking among molecules, in agreement with Wikanta [16]. Fig.…”
Section: Aloe Vera Absorptionsupporting
confidence: 80%
“…After 24 hours, all samples showed no bacterial growth inhibitory halo, or bacteriostatic, both for S. Aureus and E. Coli, according to that reported by Wikanta [16], also pattern culture medium solution Aloe Vera showed a slight bacterial growth could be due to environmental pollution, despite all the media were sterilized and previously worked in older aseptically. Those results differ from findings reported by Leon [12], in which other zones of inhibition of bacterial growth of S. Aureus in PVA/CH hydrogels with Dragon's blood solution were presented, and these films only exhibited activity against S. Aureus, while in this study no bacteriostatic or bactericidal activity was not presented to E. Coli.…”
Section: Antibacterial Activitysupporting
confidence: 76%
See 1 more Smart Citation
“…Kokabi, Sirousazar and Hassan (2007) reported that the gel fraction of PVA-clay nanocomposite was 79.4-85.0%. Wikanta, Erizal, Tjahyono, and Sugiyono (2013) also reported that the gel fraction of PVA-chitosan hydrogel was 80-85%. This gel fraction is higher compared with our result.…”
Section: Resultsmentioning
confidence: 95%
“…Sedangkan material yang tidak terlarut yang didapatkan lalu dikeringkan, dioven pada suhu 50⁰C selama 24 jam. Fraksi gel ditentukan dari rasio berat antara gel kering yang tidak terlarut dan berat awal hydrogel [7]. Fraksi gel : (Wc/Wo) x 100%.…”
Section: 4unclassified